2023
DOI: 10.1007/s11270-023-06343-3
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Immunopathological Alterations of Clarias gariepinus Exposed to Monocyclic Aromatic Hydrocarbons (BTX)

Abstract: This study’s goal was to assess the catfish’s response to exposure to monoaromatic petroleum hydrocarbons (benzene, toluene, and xylene) and its recovery after exposure using oxidative stress, histopathological, and immunological changes as biomarkers. Four groups: one as control and other three exposed to benzene (0.762 ng/L), toluene (26.614 ng/L), and xylene (89.403 ng/L), respectively, for 30 days and then recovery period for 30 days. The levels of the cortisol, lipid peroxidation, and cytokines (IL-1β, IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 80 publications
1
3
0
Order By: Relevance
“…The histopathological abnormalities in the liver and kidney of exposed groups are in the same line with those reported in the studies of Sayed et al 7 , 8 . As a consequence of loss of antioxidant defensive shield to fight damaging free radicals and increase in death-mediated proteoses 52 , 53 , and following the observations of Sayed et al 7 , 54 , our results revealed presence of necrotic alterations in the liver of benzene group and epithelial sloughing in the kidney of benzene and toluene groups.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The histopathological abnormalities in the liver and kidney of exposed groups are in the same line with those reported in the studies of Sayed et al 7 , 8 . As a consequence of loss of antioxidant defensive shield to fight damaging free radicals and increase in death-mediated proteoses 52 , 53 , and following the observations of Sayed et al 7 , 54 , our results revealed presence of necrotic alterations in the liver of benzene group and epithelial sloughing in the kidney of benzene and toluene groups.…”
Section: Discussionsupporting
confidence: 90%
“…The levels of antioxidant enzymes in the liver were higher in fish treated with benzene as opposed to those treated with toluene and xylene. The heightened toxicity of benzene attributed to its elevated vapor pressure 8 . Another investigation explored the response of Clarias gariepinus to exposure to monoaromatic petroleum hydrocarbons, utilizing oxidative stress, histopathological changes, and immunological alterations as biomarkers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations